Effect of extracellular enzyme activity on digestion performance of mesophilic UASB reactor treating high-strength municipal wastewater - Turkdogan-Aydinol, F. Ilter; Yetilmezsoy, Kaan; Comez, Sezen (SPRINGER, 2011)
Effect of extracellular enzyme activity on digestion performance of up-flow anaerobic sludge blanket (UASB) reactor was investigated for enhancement of anaerobic treatability of municipal wastewater. Two identical UASB reactors (9 L), namely Reactor-A (without enzyme addition) and Reactor-B (with enzyme addition), were simultaneously operated at mesophilic conditions (32 +/- A 2 A degrees C) with a hydraulic retention time of 24 h. Preliminary test results showed that the highest total chemical oxygen demand (TCOD) removal were achieved with an extracellular enzyme dosage of 0.2 mL/L. In the activation period of the extracellular enzyme (on days 186-212), while Reactor-A removed up to 69.3% of TCOD and 55.9% of soluble chemical oxygen demand (SCOD), Reactor-B effectively removed up to 81.9% of TCOD and 72.2% of SCOD. The average VFA/alkalinity ratios were determined to be about 0.40 (+/- 0.03) and 0.28 (+/- 0.08) for Reactor-A and Reactor-B, respectively.
Keywords: Municipal wastewater; Up-flow anaerobic sludge blanket; Extracellular enzyme; Mesophilic temperature; Statistical analysis; ANAEROBIC BAFFLED REACTOR; START-UP; HYDROLYTIC ENZYMES; PILOT-PLANT; SOLID-WASTE; SLUDGE; REMOVAL; SEWAGE; TEMPERATURE; IMPROVEMENT; Biotechnology & Applied Microbiology; Engineering